THE EFFECTIVENESS OF ONLINE LEARNING PLATFORMS IN HIGHER EDUCATION: A COMPREHENSIVE ANALYSIS - SAJAD AHMAD MALIK (RADJA PUBLIKA, 2023)
ABSTRACT The landscape of higher education has witnessed a transformative shift with the widespread adoption of online learning platforms. This study provides a comprehensive analysis of the effectiveness of online learning in higher education, examining its impact on student engagement, learning outcomes, and institutional dynamics. Through a mixed-methods approach, combining quantitative surveys, academic performance analysis, qualitative interviews, and case studies, the study aims to offer nuanced insights. The literature review explores existing research on online learning effectiveness, drawing on global perspectives and specific cases within the Indian context. Case studies from institutions such as the Indian School of Business, SWAYAM, Manipal Academy of Higher Education, and NPTEL highlight diverse approaches, best practices, and lessons learned. Quantitative data analysis involves descriptive statistics, correlation analysis, and comparative assessments to understand relationships between variables. Qualitative data, obtained through interviews and focus groups, undergoes thematic and content analysis to provide rich insights into participant experiences. The case studies showcase the success of various models, emphasizing the role of technology, industry collaboration, and inclusive design. The research identifies challenges such as the digital divide, faculty readiness, and quality assurance, proposing recommendations for future action. The findings contribute to the ongoing discourse on online learning effectiveness, offering valuable insights for educators, policymakers, and institutions. The research underscores the transformative potential of online education, provided strategic investments are made in technology, faculty development, and inclusive practices, ensuring that higher education remains accessible, relevant, and responsive to the evolving needs of diverse learners.